Remaking the Song : Operatic Visions and Revisions from Handel to Berio - Parker, Roger, 1951- (Book collections on Project MUSE., 2006)
Spanning almost the entire history of opera, this book re-examines attitudes toward some of our best-loved musical works, and asks a question: what exactly is opera? It considers the works by Handel, Mozart, Donizetti, Verdi, Wagner, Puccini, and Berio, aiming to challenge what many regard as sacroscant: the opera's musical text.